Modern German Scientific and Technical Terminology: Main Methods and Models Formation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is aimed at identifying the features of the formation of German language based on professional technical literature. The relevance of the study material is beyond doubt, since today in digital world many processes in human life are carried out using computers or mobile technology, every day more and more electronic systems and applications appear, which, in turn, cannot but affect the language.